2009
DOI: 10.1016/j.tecto.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Shape and amount of the Quaternary uplift of the western Rhenish shield and the Ardennes (western Europe)

Abstract: a b s t r a c t a r t i c l e i n f oA good evaluation of the Quaternary uplift of the Rhenish shield is a key element for the understanding of the Cenozoic geodynamics of the western European platform in front of the alpine arc. Previous maps of the massif uplift relied on fluvial incision data since the time of the rivers' Younger Main Terrace to infer a maximum post-0.73 Ma uplift of~290 m in the SE Eifel. Here, we propose a new interpretation of the incision data of the intra-massif streams, where anomalie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 50 publications
0
22
0
6
Order By: Relevance
“…This stress field caused strong subsidence in the North-Sea basin and uplift of the Mesozoic and Palaeozoic bedrock south of the North German Lowlands (Cloetingh et al, 1990;Ziegler et al, 1995). Reconstructed uplift rates since the Middle Pleistocene for the Ardennes and Rhenish Massif range between 0.03 and 0.25 m/ka (e.g., Veldkamp and Van den Berg, 1993;Veldkamp and Van Dijke, 2000;Demoulin and Hallot, 2009) and 0.05e0.06 m/ka for northern France (Antoine et al, 2007). For the Aller valley, an eastern tributary of the River Weser, Veldkamp et al (2002) reconstructed uplift rates between 0.03 and 0.06 m/ka, but suggested that these values may be underestimated because the upper River Aller has been unable to compensate all crustal uplift.…”
Section: Structural Settingmentioning
confidence: 99%
“…This stress field caused strong subsidence in the North-Sea basin and uplift of the Mesozoic and Palaeozoic bedrock south of the North German Lowlands (Cloetingh et al, 1990;Ziegler et al, 1995). Reconstructed uplift rates since the Middle Pleistocene for the Ardennes and Rhenish Massif range between 0.03 and 0.25 m/ka (e.g., Veldkamp and Van den Berg, 1993;Veldkamp and Van Dijke, 2000;Demoulin and Hallot, 2009) and 0.05e0.06 m/ka for northern France (Antoine et al, 2007). For the Aller valley, an eastern tributary of the River Weser, Veldkamp et al (2002) reconstructed uplift rates between 0.03 and 0.06 m/ka, but suggested that these values may be underestimated because the upper River Aller has been unable to compensate all crustal uplift.…”
Section: Structural Settingmentioning
confidence: 99%
“…During the Late Pleistocene, vertical slip rates within this range of values along the border faults of the Roer Valley Graben were shown by paleoseismic investigations on the Peelrand and the Feldbiss fault zones [Camelbeeck and Meghraoui, 1998;Vanneste et al, 1999;Vanneste and Verbeeck, 2001;van den Berg et al, 2002;Camelbeeck et al, 2007]. The pronounced river incision in the Rhenish shield and its present-day elevation also suggest a significant uplift during the Quaternary [Demoulin and Hallot, 2009]. Our question is whether it is possible to detect such an elevation of the Rhenish shield, possibly related to rift shoulder uplift in response to rifting in the Roer Graben System.…”
Section: Discussionmentioning
confidence: 86%
“…On a larger scale, the RM and adjoining areas are deformed and uplifted due to the development and evolution of the ECRIS (represented by the Lower Rhine Graben (LRG) and the Upper Rhine Graben (URG) in Figure 1b) since the Eocene about 40 Ma ago (Bourgeois et al 2007;Demoulin and Hallot 2009;Fuchs et al 1983;Schmincke 2007;Dèzes et al 2004;Ziegler and Dèzes 2007;and references therein). Intensified tectonic activity in the last 700 ka is expressed by the accelerated uplift of the RM and young volcanism in the Eifel region (Demoulin and Hallot 2009;Fuchs et al 1983;Meyer and Stets 2002;Schmincke 2007). …”
Section: Cenozoic Evolutionmentioning
confidence: 99%